Extracellular vesicles secreted by bone marrow- and adipose tissue-derived mesenchymal stromal cells fail to suppress lymphocyte proliferation - Andrade, Ana Valéria Gouveia de; Bieback, Karen (Stem Cells and Development, 2015)
Recently, mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) have been suggested as an alternative to MSCs for the treatment of various inflammatory disorders. However, while a first case report observed beneficial therapeutic effects of repeated MSC-EV infusions in a patient with therapy-refractory graft-versus-host disease, in vitro findings revealed that MSC-EVs were significantly less immunosuppressive than their parental cells. In this study, we compared the immunosuppressive potency of MSCs derived from bone marrow (BM-MSCs) and adipose tissue (AT-MSCs), with their secreted EVs in a standardized lymphocyte proliferation assay (LPA). Both BM-MSCs and AT-MSCs exhibited a remarkable inhibition of lymphocyte proliferation (LP) (88.1%±1.5% and 75.5%±1.5%, respectively), while isolated EVs derived from them failed to suppress LP at dose levels up to 100 μg/mL. Thus, our data further substantiate previous reports suggesting that cell-cell contact plays an important role on the immunosuppressive potential mediated by MSCs. Hence, MSC-EVs are still a matter of debate and might not be a reasonable substitute for MSCs with regard to the immunosuppressive function. Collectively, these contrasting findings may also reflect the importance of relevant translational aspects when designing new studies. Standardization of MSC culture conditions before EV collection as well as isolation and characterization methods with regard to EV purity are urged. Moreover, before clinical use, dose-finding studies evaluating MSC-EV preparations in suitable preclinical models are warranted.